Investigation of the effectiveness of parent-child interaction therapy on adjustment and behavioral problems in children with subthreshold autism - Seçer, İsmail; Ulaş, Sümeyye; Tatlı, Eda; Çimen, Fatmanur; Bülbül, Burcu; Tosunoğlu, Beyzanur (Frontiers in Psychology, 2025)
BackgroundAutism Spectrum Disorder (ASD) is an increasingly prevalent neurodevelopmental disorder. However, the number of children who exhibit subthreshold levels of ASD symptoms, significant enough to experience functional and adaptive difficulties, is also substantial. These children require early interventions, similar to those diagnosed with ASD, due to their exhibited adaptive and behavioral challenges. PCIT offers a unique opportunity for children and their parents exhibiting subthreshold ASD to address such challenges through its practices and techniques.AimThis study aims to assess the initial result effectiveness of standard PCIT on the adaptive skills and school refusal behaviors of children exhibiting subthreshold ASD, as well as on the levels of parental stress and caregiving burden. The study intends to test these effects and report the outcomes.MethodThis study is a case study, and it involves three children with subthreshold ASD symptoms and their parents. The therapy processes were conducted for approximately 1 year.ResultResults obtained from this study revealed that PCIT holds promising prospects for improving adaptive and interaction skills, reducing school refusal, and alleviating parental stress and caregiving burden among children exhibiting subthreshold ASD.DiscussionPCIT is considered a functional approach for children and parents demonstrating subthreshold ASD symptoms, besides interventions addressing diagnosed ASD children. It is suggested that future studies should evaluate the effectiveness and sustainability of PCIT through randomized controlled trials in the context of subthreshold ASD.